Customer Perception and Preference towards Branded Products (with Special Reference to Television Sets) - Lilly, J. (Indian Journal of Marketing, 2010)
People begin to develop preferences at a very early age. Some babies like apple juice, others water. Some kids play softball, others read. Some people thrive in the city and some need the quiet of the country. Some drink Coke while others prefer Pepsi. Our preferences are part of what makes us who we are. And the brands we seek out reflect our preferences. The competition among brands is fierce. In every product category, consumers have more choices, more information and higher expectations than ever before. Jockeying for position in a consumer’s preference set requires an aggressive strategy and constant vigilance. The marketer’s principal objective is typically to build a relationship with buyers, rather than merely to make a single sale. Ideally, the essence of that relationship consists of a strong bond between the buyer and the brand. The choice of an individual strategy or combination depends mainly on the nature of the branded product or service. The success of the strategy depends heavily on the marketer’s understanding of the preference building and bonding process.